Density Functional Theory Study of Silolodithiophene Thiophenepyrrolopyrroledione-based Small Molecules: The Effect of Alkyl Side Chain Length in Electron Donor Materials - Seo, Dongkyun; Yoon, Youngwoon; Yeo, Hak Min; Lee, Kyung-Koo; Kim, BongSoo; Kwak, Kyungwon (WILEY-V C H VERLAG GMBH, 2015)
Push-pull small molecules are promising electron-donor materials for organic solar cells. Thus, precise prediction of their electronic structures is of paramount importance to control the optical and electrical properties of the solar cells. Various types of alkyl chains are usually introduced to increase solubility and modify the morphology of the resulting molecular films. Here, using density functional theory (DFT) and time-dependent DFT (TD-DFT), we report the precise effect of increasing the length of the alkyl chain on the electronic structure of an electron donor molecule 6,60-((4,4-dialkyl-4H-silolo[3,2-b: 4,5-b']-dithiophene-2,6-diyl)bis(thiophene- 5,2-diyl)) bis(2,5-alkyl-3-(thiophen-2-yl)-2,5-dihydropyrrolo[3,4-c] pyrrole-1,4-dione) (DTS1TDPP). Alkyl groups were attached to the bridging position (silicon atom) of the fused rings and nitrogen atom of the pyrrolopyrroledione groups. We demonstrate that the alkyl groups do not perturb the highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) energy levels, pi-delocalized backbone structure, and UV-Vis absorption spectrum when they are placed at the least steric effect positions.